PENERAPAN TEORI TECHNOLOGY ACCEPTANCE MODEL (TAM) DI RUMAH SAKIT - Jihan Syahada (Journal of Hospital Administration and Management (JHAM), 2021)
The hospital is a health service institution for the community with its own characteristics that are influenced by the development of health science, technological progress, and the socio-economic life of the community which must continue to be able to improve services that are more quality and affordable by the community in order to realize the highest degree of health. In the world of health, digitalization is very important to advance the service system in the world of health. The system is a collection/group of sub-systems/parts/components of any kind, either physical or non-physical, that are interconnected with each other and work together in harmony to achieve a particular goal. However, in the use of the system there are often obstacles in its use. Obstacles are anything that hinders, hinders, hinders that humans encounter. To find out these obstacles, research is needed on the theory of user acceptance of information systems. Technology Acceptance Model (TAM) is a user theory in the acceptance of information systems. The aim is to provide an explanation of the determinants of computer acceptance, to be able to describe user behavior in various end-user computing technologies and a population of information system users. so that researchers can identify a particular system may be unacceptable, and pursue appropriate corrective steps. The purpose of using TAM is to provide a basis for tracking the impact of external factors on internal beliefs, attitudes, and intentions. The Technology Acceptance Model (TAM) was formulated in an attempt to achieve this goal by identifying a small number of fundamental variables suggested by related previous studies.